Small bowel capsule endoscopy revealing neuromuscular and vascular hamartoma of the jejunum: A case report. Issue 15 (April 2018) - Caruso, Maria L.; Cavalcanti, Elisabetta; De Michele, Francesco; Ignazzi, Antonia; Carullo, Roberta; Mastronardi, Mauro
Abstract: Rationale: Digestive hemorrhage is a life-threatening and represents for both clinicians and patient a challenger problematic condition with the urgencies to discover the origin for correct the cause and safe the life of patient. Patient concerns: We report the case of a 58 -year-old man with extremely rare hamartomatous neurovascular lesion. Following recurrent episode of intestinal hemorrhage the patient underwent small bowel capsule endoscopy. Diagnoses: Diagnosed with small intestine neoplasia. Interventions: The patient underwent curative small bowel resection. Histologic diagnosis was neuromuscular and vascular hamartoma (NMVH). In the small intestine, neoplastic lesions are very rare (2%) and mostly malformative while the more frequent cause of cryptic digestive hemorrhage remains angiodysplasia (50%) . The preexisting NMVH was exacerbated by the use of non-steroidal anti-inflammatory drugs, causing hemorrhage due to diffuse ulceration. Outcomes: The patient stay healthy after treatment. Lessons: This is an hemorrhagic lesion with macroscopic "neoplastic" patterns due to abnormal mixing of normal indigenous tissue components. It poses a diagnostic challenge for clinicians and pathologists, but diagnosis is facilitated by capsule endoscopy and surgical treatment should provide definitive resolution.